Design and Development of Preservative Free Herbal Dosage Forms - Pushpalatha, H.B.; Kumar, T.M. Pramod; Padiyar, U. Aravind; Sundaram (Natural Products Journal, The, 2014)
This review focuses on principles of product preservation, preservatives, and novel technologies for the future development of preservative free herbal products. The purpose of this study was to determine the amount of preservatives in pharmaceutical products as some recent studies reported serious side effects associated with the ingestion of these substances. The principles involved were asepsis and removal of microorganisms — both static and cidal effects. Some of the novel technologies of asepsis are high pressure processing, pulsed electric field treatment and non-thermal technologies including ultraviolet processing. All relevant literature databases were searched upto 2011. Majority of the human, animal, in vitro studies, and reviews were included. Preservative free dosage forms must be formulated for the reduction in side effects and hence a healthier mankind.
Keywords: pasteurization